Optical propagation in linear media : atmospheric gases and particles, solid state components, and water - Thomas, Michael Eugene, 1951- (Johns Hopkins University/Applied Physics Laboratory series in science and engineering., 2006)
PART I: Background Theory and Measurement. 1. Optical Electromagnetics I. 2. Optical Electromagnetics II. 3. Spectroscopy of Matter. 4. Electrodynamics I: Macroscopic Interaction of Light and Matter. 5. Electrodynamics II: Microscopic Interaction of Light and Matter. 6. Experimental Techniques. PART II: Practical Models for Various Media. 7. Optical Propagation in Gases and the Atmosphere of the Earth. 8. Optical Propagation in Solids. 9. Optical Propagation in Liquids. 10. Particle Absorption and Scatter. 11. Propagation Background and Noise.